ANALYSIS OF INTERSECTION PERFORMANCE AND NOISE LEVELS AT TANJUNG BARU - NAN SARUNAI INTERSECTION, TABALONG REGENCY - Maulana, Muhammad Hafiz; Arsyad, Muhammad (CERUCUK, 2026)
The Tanjung Baru - Nan Sarunai four-way intersection, a strategic non-signalized junction connecting the national roads of South, Central, and East Kalimantan, experiences significant traffic congestion due to heavy vehicle flows, particularly mining employee fleets. This study employs the 2023 Indonesian Highway Capacity Guidelines (PKJI 2023) and Excel-based calculations using geometric intersection data, traffic volume, noise levels, and population data from Tabalong Regency.            The peak traffic hour was identified between 3:10 PM and 4:10 PM WITA, with existing conditions showing Dj = 0.30, T = 8.48, and Pa = 9.10%. A 21-year traffic forecast indicates increased congestion (Dj = 0.86, T = 14.70, Pa = 43.99%). Proposed alternatives, including lane widening and signalization, yielded a service level index of C (Dj = 0.82, T = 20.06, TLL = 37.4). Peak noise levels reached 100.9 dB at the intersection and 92.8 dB in the surrounding area, with strong correlation values observed (R = 0.76 for the intersection; R = 0.56 for the area). Keywords: Indonesian Road Capacity Guidelines (PKJI 2023), Forecasting, APILL Intersection, Level of Service Index, Capacity, Degree of Saturation, Delay Time, Queue Probability, Noise Level, and Correlation.